Spatio-temporal Variation and Influencing Factors of CO2 Emission at County Scale in Shaanxi Province Based on Land Use Change - Cao Zhouliang; Zhang Xinrong; Yuan Xuefeng; Chen Jinhong (Shuitu baochi tongbao)
[Objective] The spatio-temporal changes and influencing factors of carbon emission at the county scale in Shaanxi Province from 2000 to 2020 were analyzed in order to provide a reference for ecological civilization construction and low-carbon sustainable development in Shaanxi Province. [Methods] Socioeconomic and land use data were used to construct a carbon emission estimation model. The total carbon emission in Shaanxi Province was calculated and the spatiotemporal patterns and changes from 2000 to 2020 were analyzed. Subsequently. The influencing factors of carbon emissions were determined using the geographically weighted regression method. [Results] ① Total carbon emissions increased from 3.30×107 tons in 2000 to 1.93×108 tons in 2020. The evolution of carbon emission can be divided into two stages (substantial growth and slow growth). ② The carbon emission center gradually moved to the northeast from 2000 to 2020, and the spatial distribution range showed an expansion trend. The hot spots were mainly located in the northern counties of Yulin City, and around Xi'an and Xianyang City. The cold spots were mainly located in Foping County and Shiquan County. ③ Per capita GDP, land use degree, and per capita total social retail sales were positively correlated with carbon emissions, while industrial structure and population density were negatively correlated in 60.74% and 92.52% of counties, respectively. [Conclusion] Low-carbon development should be promoted in Shaanxi Province by formulating differentiated regional carbon emission reduction plans, optimizing the land use structure, controlling the expansion of construction land, and by enhancing public awareness of low-carbon environmental protection.